Phenetic relationship of Genus Knema, Horsfieldia, and Myristica in Java based on pollen morphological evidence - ARRIJANI ARRIJANI (Biodiversitas Journal of Biological Diversity, 2003)
The main purposes of the research were to support taxonomic evidence data in particular of palinology spesies classified inMyristicaceae family at Java and determine phenetic relationship as an effort of increasing objectivity and repeatability of classification result. Pollen was collected in Herbarium Bogoriense and Bogor Botanical Garden, and prepared for light and Scanning Electron Microscope. Acetolysis method was used for light microscopy of the pollen preparation, and coating with gold was prepared for SEM. Phenetic relationship determined using coefficients of correlation and association.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: phenetic relationship, pollen morphology, Knema, Horfieldia, and Myristica.